The clever strategy of a tiny crustacean eye early in the evolution of vision - Schoenemann, Brigitte (Landes Bioscience, 2012)
Henningsmoenicaris scutula (Walossek and Müller, 1990) (Fig. 1) is a tiny representative of Crustacea, systematically standing close to the stemline. It is found in stinkstone (‘Orsten’) nodules from the Alum Shale, where a rich fauna of small organisms is excellently preserved. Three dimensional morphology is retained by phosphatisation, which exhibits the finest details, such as cuticular structures, fine appendages and especially the morphology of the compound eyes. The stalked eyes of H. scutula investigated here were equipped with a differentiated visual surface with four different areas of vision. The most intriguing is a field of view oriented laterally to the contralateral side of each eye, so that the fields of view of both compound eyes intersect, and give information about any object moving within the vicinity. Due to this, although, for various reasons this compound eye probably was not able to form a proper image, it was able to perceive tiny prey within a wide visual field, in the same way that the movement of figures can be traced in a chess game. This can be considered as a highly sophisticated visual system that developed early in the history of reported eye evolution, as this compound eye is almost exactly half a billion years old.